Sensitivity analysis of buckling loads of physically non-linear frames using dynamic and static criteria - Garstecki, Andrzej; Glema, Adam (Zielona Góra: Uniwersytet Zielonogórski)
Small eigenvibrations around the prestressed equilibrium state are considered and the sensitivity of eigenfrequencies with respect to cross-sectional parameters of the frame is assessed. The sensitivity operators thus derived are used to determine the sensitivity of buckling load with dynamic criterion. For comparison, the static criterion is employed, too.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka